Sexual behaviour of people living with HIV attending a tertiary care government hospital in Kathmandu, Nepal: a cross sectional study - Angdembe, Mirak Raj (BMC Res Notes, 2015)
BACKGROUND: Clinical improvements that follow antiretroviral therapy (ART) may lead to increase or resumption of high risk activities that could unintentionally result in HIV transmission. The objective was to investigate whether treatment status is a significant predictor of sexual risk behaviour (unprotected sex). METHODS: A cross sectional study was conducted among 160 people living with HIV (PLHIV) (89 ART experienced and 71 ART naïve) attending Sukraraj Tropical and Infectious Disease Hospital in Kathmandu, Nepal. A structured questionnaire was used for data collection. Logistic regression with stepwise modeling was used to obtain adjusted odds ratios (OR) with 95 % CI. RESULTS: In this study, 92 % of sexually active respondents reported sex with a regular partner. ART experienced PLHIV were significantly more likely to report consistent condom use with their regular partners compared to ART naïve PLHIV (83 vs. 53 %; P = 0.006) during the past six months. In multivariate analysis, sex (OR = 4.59, 95 % CI: 1.15–18.39), treatment status (OR = 4.76, 95 % CI: 1.29–17.52) and alcohol consumption during last sex with regular partners (OR = 14.75, 95 % CI: 2.75–79.29) were significantly associated with unprotected sex. CONCLUSION: ART naïve PLHIV were five times more likely to exhibit sexual risk behaviour (have unprotected sex) than ART experienced PLHIV. Thus the study provided no evidence to suggest that ART experienced PLHIV exhibit greater sexual risk behaviour compared to ART naïve PLHIV. Prevention programmes need to emphasize on counselling to PLHIV and their regular partners with focused interventions such as couple counselling and education programmes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-015-1559-0) contains supplementary material, which is available to authorized users.